Ln*(x-4)+ln*(x-7)=ln*18

Simple and best practice solution for Ln*(x-4)+ln*(x-7)=ln*18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln*(x-4)+ln*(x-7)=ln*18 equation:


Simplifying
Ln(x + -4) + ln(x + -7) = ln * 18

Reorder the terms:
nL(-4 + x) + ln(x + -7) = ln * 18
(-4 * nL + x * nL) + ln(x + -7) = ln * 18
(-4nL + nxL) + ln(x + -7) = ln * 18

Reorder the terms:
-4nL + nxL + ln(-7 + x) = ln * 18
-4nL + nxL + (-7 * ln + x * ln) = ln * 18
-4nL + nxL + (-7ln + lnx) = ln * 18

Reorder the terms:
-7ln + lnx + -4nL + nxL = ln * 18

Reorder the terms for easier multiplication:
-7ln + lnx + -4nL + nxL = 18ln

Solving
-7ln + lnx + -4nL + nxL = 18ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-18ln' to each side of the equation.
-7ln + lnx + -4nL + -18ln + nxL = 18ln + -18ln

Reorder the terms:
-7ln + -18ln + lnx + -4nL + nxL = 18ln + -18ln

Combine like terms: -7ln + -18ln = -25ln
-25ln + lnx + -4nL + nxL = 18ln + -18ln

Combine like terms: 18ln + -18ln = 0
-25ln + lnx + -4nL + nxL = 0

Add '4nL' to each side of the equation.
-25ln + lnx + -4nL + 4nL + nxL = 0 + 4nL

Combine like terms: -4nL + 4nL = 0
-25ln + lnx + 0 + nxL = 0 + 4nL
-25ln + lnx + nxL = 0 + 4nL
Remove the zero:
-25ln + lnx + nxL = 4nL

Add '-1nxL' to each side of the equation.
-25ln + lnx + nxL + -1nxL = 4nL + -1nxL

Combine like terms: nxL + -1nxL = 0
-25ln + lnx + 0 = 4nL + -1nxL
-25ln + lnx = 4nL + -1nxL

Reorder the terms:
-25ln + lnx + -4nL + nxL = 4nL + -4nL + -1nxL + nxL

Combine like terms: 4nL + -4nL = 0
-25ln + lnx + -4nL + nxL = 0 + -1nxL + nxL
-25ln + lnx + -4nL + nxL = -1nxL + nxL

Combine like terms: -1nxL + nxL = 0
-25ln + lnx + -4nL + nxL = 0

Factor out the Greatest Common Factor (GCF), 'n'.
n(-25l + lx + -4L + xL) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing l to the left, all other terms to the right. Add '-1n' to each side of the equation. n + -1n = 0 + -1n Remove the zero: 0 = -1n Simplifying 0 = -1n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-25l + lx + -4L + xL)' equal to zero and attempt to solve: Simplifying -25l + lx + -4L + xL = 0 Reorder the terms: -4L + -25l + lx + xL = 0 Solving -4L + -25l + lx + xL = 0 Move all terms containing l to the left, all other terms to the right. Add '4L' to each side of the equation. -4L + -25l + lx + 4L + xL = 0 + 4L Reorder the terms: -4L + 4L + -25l + lx + xL = 0 + 4L Combine like terms: -4L + 4L = 0 0 + -25l + lx + xL = 0 + 4L -25l + lx + xL = 0 + 4L Remove the zero: -25l + lx + xL = 4L Add '-1xL' to each side of the equation. -25l + lx + xL + -1xL = 4L + -1xL Combine like terms: xL + -1xL = 0 -25l + lx + 0 = 4L + -1xL -25l + lx = 4L + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 | | 2(2x-1)-3(x+3)=x+1 | | 7y+8y-3x-4x= | | 2x-25+7x-75=7x-20 | | 7x-x^3=6 | | 9x+3y-6x+2y= | | 4w+10=-3(w-8) | | 25x+7x-4x-6x= | | Sinx=-.72 | | 2(d+6)=-2d-12 | | X+40+y=180 | | 2x+33=7x+3 | | 0.84xa=1 |

Equations solver categories